Advertisement

One more thing:  If you start with something like

12x = -2x^3 - 10x^2


ALWAYS move stuff around so your biggest power guy is positive.

12x = -2x^3 - 10x^2

Check it out:

12x = -2x^3 - 10x^2 ... add ( 2x^3 + 10x^2 ) to both sides, which gives 2x^3 + 10x^2 + 12x = 0

Now, we can solve it!

Factor: 2x ( x^2 + 5x + 6 ) = 0 which gives 2x ( x + 2 ) ( x + 3 ) = 0

Blobs = 0: 2x = 0 or x + 2 = 0 or x + 3 = 0 , which gives x = 0 or x = -2 or x = -3

{ -3, -2, 0 }


YOUR TURN:

Solve  -16x = -4x^3